Pesan Dakwah Melalui Tradisi Jamu Laut Pesisir Pantai Kelurahan Sei Berombang - Syafruddin Al Hafiz; Rubino (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to explore, describe, and analyze the messages of da'wah contained in the Jamu Laut tradition in the coastal community of Sei Berombang Village. The formulation of the research problem includes how the process of implementing the Jamu Laut tradition in Sei Berombang Village and what are the da'wah messages contained in the tradition in terms of faith, sharia, and morals. This study uses a qualitative method with an ethnographic approach, in which researchers describe, explain, and analyze the da'wah messages in the series of Jamu Laut traditions from the perspective of local community leaders. Data were collected through interviews with community leaders to understand the meaning and values ??contained in each series of Jamu Laut traditions, taking into account the local context and perspective. The results of the study show that the Jamu Laut tradition is carried out in several systematic stages starting from deliberation and the formation of a committee to the evening event on land with the reading of dhikr and prayers together. This tradition contains a comprehensive message of da'wah including aspects of aqidah (belief in Allah, angels, books, messengers, the Day of Judgment, and qadar), aspects of sharia (fair practices of worship and muamalah), as well as aspects of morals (towards Allah, fellow humans, and the environment). The Jamu Laut tradition is a manifestation of harmonization between Islamic values ??and local wisdom which is preserved as a form of gratitude to Allah SWT for the blessings of sustenance and safety from the sea.